(untitled) (UK and Ireland Engineering Education Research Network Conference Proceedings 2023, 2024)
In recent years, there has been a significant shift towards providing comprehensive support to university students for their professional development, transferable skills, and employability. Capstone projects play a pivotal role in bridging the gap between academic learning and practical application, equipping students to navigate the challenges of their future careers (Fung, 2017) . These projects often serve as a reflection of students’ growth and development, with successful completion signifying the acquisition of essential skills and knowledge in their chosen field of study. This engineering education practice paper explores the latest developments in engineering capstone project coordination, tutoring, and assessment, with a specific focus on enhancing student wellbeing. These practices aim to equip students with greater resilience, improved employability, and stronger teamwork skills, essential in the dynamic and diverse field of engineering. The intervention showcased here represents a significant enhancement for the 2022-2023 academic year in reinforcing the structure of capstone projects within the Department of Electronic and Electrical Engineering at The University of Sheffield. Initial findings indicate improvements in student wellbeing and interpersonal skills due to well-structured tutoring support and clear module deliverables guidelines.